2008
DOI: 10.1142/s0218301308010507
|View full text |Cite
|
Sign up to set email alerts
|

Open and Hidden Charm in Proton–nucleus and Heavy-Ion Collisions

Abstract: We review the collectivity and the suppression pattern of charmed mesons -produced in proton-nucleus and nucleus-nucleus collisions at SPS (∼ 158 A·GeV) and RHIC energies (∼ 21 A·TeV) -in comparison to dynamical and thermal models. In particular, we examine the charmonium 'melting' and the 'comover dissociation' scenarios -implemented in a microscopic transport approach -in comparison to the available data from the SPS and RHIC. The analysis shows that the dynamics of c,c quarks at RHIC are dominated by parton… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 179 publications
5
98
0
Order By: Relevance
“…This branching ratio is two orders of magnitude smaller than the corresponding decay into a φ meson. First we can compare the obtained Λ c and J/Ψ production cross sections with previous near threshold estimates [46,47], as shown in figures 4 and 5. Our estimates are in reasonable agreement (J/Ψ) or even very conservative estimates (Λ c ) as compared to previous work.…”
Section: Charming Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…This branching ratio is two orders of magnitude smaller than the corresponding decay into a φ meson. First we can compare the obtained Λ c and J/Ψ production cross sections with previous near threshold estimates [46,47], as shown in figures 4 and 5. Our estimates are in reasonable agreement (J/Ψ) or even very conservative estimates (Λ c ) as compared to previous work.…”
Section: Charming Resultsmentioning
confidence: 69%
“…We can utilize the decays of the most massive N * resonances implemented in UrQMD, namely the N * → N + φ p+p->D+D+X SIS100 Figure 5. Comparison of the J/Ψ production yield in p+p and central A+A collisions from the UrQMD approach (symbols) with previous theoretical estimates (green short dashed) [47].…”
Section: Strange Resultsmentioning
confidence: 91%
“…10. On the other hand, simulations in transport theory [75] have shown that the local energy densities achieved in the course of heavy-ion collisions at SPS and RHIC energies reach at most 20 GeV/fm 3 ; this region is high-lighted in Fig. 10 by a shadowed area.…”
Section: Contributions Of the Different Processes To The Dileptonmentioning
confidence: 97%
“…To model the initial state for the J/Ψ-particles one needs the momentum distribution and the spatial distribution at the production points. For the momentum distribution of the produced charmonia at SPS we use an ansatz from [34].…”
Section: The Model and Resultsmentioning
confidence: 99%
“…The exponent for the transverse distribution is b pT = 2.08 GeV −1 [34]. Our spatial distribution for the charmonium production at SPS is based on the Glauber model and calculated using the UrQMD model.…”
Section: The Model and Resultsmentioning
confidence: 99%